Influencing Factors of Health Management Practices for Older Adults Contracted by Family Doctors in Rural Areas of China: a Scoping Review - LIU Haiyan, NING Yanhua, KONG Weijuan, GUO Yahong, SHI Jing, LIU Lingna, LYU Xiongxiong, LI Meiman (Zhongguo quanke yixue)
Background Health management based on family doctors' contract service is an essential approach for promoting healthy aging for rural older adults in China, yet its implementation is influenced by various factors. Objective To summarize influencing factors of health management for older adults contracted by rural family doctors in China, providing the basis of reference for the accessibility and effectiveness. Methods From January to April 2023, the PRISMA-ScR checklist was used. Studies on health management by family doctor contract service were searched from databases of Web of Science, PubMed, Embase, Medline, CINAHL, CNKI, Wanfang Data, VIP, and CBM from inception to December 2022, and enrolled according to the inclusion and exclusion criteria. Relevant data were extracted, collected, summarized and reported guided by the Social Ecological Model. Results A total of 27 articles were included. We extracted 5 levels of influencing factors related to health management for older adults by family doctors contracted service in rural areas, including individual, interpersonal, organizational, community and policy. Conclusion The implementation of health management for older adults contracted by rural family doctors is influenced by multiple factors. To promote the development of health management for older adults in rural areas, it is necessary to comprehensively consider these influencing factors, clarify the rights and responsibilities of relevant departments and parties, and jointly promote the improvement of the quality and efficiency of health management services based on family doctor contract services.